2001
DOI: 10.1007/bf02723245
|View full text |Cite
|
Sign up to set email alerts
|

Association between lower hair zinc levels and Neural Tube Defects

Abstract: Though folic acid supplementation has reduced the incidence of Neural Tube Defects (NTD), NTD still constitutes one of the important congenital malformations having wide medical, social and ethical implications. Zinc deficiency has been reported to produce NTD in animals. This study was designed to evaluate zinc status of the newborn babies with NTD and their mothers. Eighty newborn babies with NTD and their mothers served as cases. Eighty apparently normal newborn babies and their mothers served as controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The group of 18 women used to estimate dietary folate intake was small, but comparison of our data with the National Survey [40] gave values almost identical to ours (Table IV).…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 77%
See 1 more Smart Citation
“…The group of 18 women used to estimate dietary folate intake was small, but comparison of our data with the National Survey [40] gave values almost identical to ours (Table IV).…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 77%
“…Justification of .700 mg /day as a standard for optimal TFI is based on the assumption that optimal lowering of homcysteine reduces the risk of NTD to near zero for most women [31,32], but 20-30% of women may need .4000 mg /day or may have a NTD aetiology that does not respond to any dose of FA [35,36,40].…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…Results of a study in Turkey showed newborn serum zinc and selenium to be low in NTDs compared to normal controls (26). An Indian study that evaluated maternal and newborn hair zinc levels in association with NTDs found that the hair zinc levels in both mothers and newborns were significantly low compared to normal controls and recommended a follow-up study with zinc supplementation in the periconceptional period and outcome in the subsequent pregnancy (27). …”
Section: Discussionmentioning
confidence: 99%
“…Zn is critical for many processes involved in CNS development, such as neurogenesis, neuronal migration, and synaptogenesis and its deficiency could interfere with neurophysiological development (22)(23)(24). In humans, mild maternal Zn deficiency, assessed by serum and hair Zn, is associated with an increased frequency of neural tube defects, which may subsequently impair brain development (25). Zn deprivation in immature animals has been demonstrated to impair behavior, including learning, attention, and memory (26) similar to the effects of prenatal ethanol exposure.…”
mentioning
confidence: 99%